Kearns-Sayre Syndrome: A Rare Mitochondrial Deletion Disorder - Roy, B; Mondal, G; Nanda, D; Das, S; Das, MK (Journal of Nepal Paediatric Society, 2013)
A 9 yr girl presented with bilateral ptosis and deafness of gradual onset for the last four years. Associated ophthalmoplegia and pigmentary retinopathy, heart block, raised CSF protein and serum lactate was suggestive of the diagnosis of Kearns-Sayre syndrome (KSS), a rare entity in the spectrum of the mitochondrial deletion syndrome. Search for endocrinopathy revealed no abnormality. DOI: http://dx.doi.org/10.3126/jnps.v33i1.6696 J Nepal Paediatr Soc. 2013;33(1):61-62